-6(8-5r)=-r-6(1-4r)

Simple and best practice solution for -6(8-5r)=-r-6(1-4r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(8-5r)=-r-6(1-4r) equation:


Simplifying
-6(8 + -5r) = -1r + -6(1 + -4r)
(8 * -6 + -5r * -6) = -1r + -6(1 + -4r)
(-48 + 30r) = -1r + -6(1 + -4r)
-48 + 30r = -1r + (1 * -6 + -4r * -6)
-48 + 30r = -1r + (-6 + 24r)

Reorder the terms:
-48 + 30r = -6 + -1r + 24r

Combine like terms: -1r + 24r = 23r
-48 + 30r = -6 + 23r

Solving
-48 + 30r = -6 + 23r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-23r' to each side of the equation.
-48 + 30r + -23r = -6 + 23r + -23r

Combine like terms: 30r + -23r = 7r
-48 + 7r = -6 + 23r + -23r

Combine like terms: 23r + -23r = 0
-48 + 7r = -6 + 0
-48 + 7r = -6

Add '48' to each side of the equation.
-48 + 48 + 7r = -6 + 48

Combine like terms: -48 + 48 = 0
0 + 7r = -6 + 48
7r = -6 + 48

Combine like terms: -6 + 48 = 42
7r = 42

Divide each side by '7'.
r = 6

Simplifying
r = 6

See similar equations:

| 5*2+10-5x=205 | | x+2x-4x=16 | | 5*2+5x=18 | | 6*2+2x=12 | | 16x+44=0 | | 3k^2-28=-17 | | 3x^2-12x+39=5 | | X+7z=24 | | 7p^2-16p-21=-6 | | 9+81= | | 50a^2*41=2a^4+5000 | | 1500/x | | 50x^2*41=2x^4+5000 | | 9n^2-4=572 | | 0=x(6x-18) | | Y=x(6x-18) | | X-.05x=360640 | | -5(5b-4)+2(9b+2)= | | 9(z+2)-4z(3z+5)= | | 4=-16t^2+96t+4 | | 30*0.2x=45+3(x) | | 3p(8+2p)-p(2p-3)= | | 4/7t-1/14t=t-17/2 | | b(3+3b)-b(2b-3)= | | 0.25m+0.5+0.75m=1.5m | | -2(w+14)=-12 | | 3v-6=6 | | 6+6z-1=9z+12-2z | | 2(9s+11)-3s=3(5s+4)-14 | | 50x^2*41-5000=2x^4 | | -6(6z-1)+8(z+4)= | | 0.2(x+100)+0.6x=36 |

Equations solver categories